AN ACADEMIC STUDY AND LITERARY RESEARCH INTO WORKS OF SHUKUR KHALMIRZAYEV (British Journal of Global Ecology and Sustainable Development, 2022)
This article presents a systematic analysis of the study of life and work of Shukur Khalmirzayev, the outstanding representative of Uzbek literature of the XX century with honorary title of “People’s writer”. In fact, since he was a multifaceted writer, the article reveals his contribution to the development of various genres of prose - novel, short story, novel, essay, as well as drama and journalism. It is pointed out that Shukur Khalmirzayev created a new school in the genre of story in Uzbek national literature. He was emphasized as the owner of a rare talent as a  result of a consistent analysis, study of the stages of formation of the writer’s work, his contribution to domestic and world literature.